A PARAMETRIC DESCRIPTION OF DEONTIC MODALITY IN THE POLISH AND SPANISH CIVIL CODES - NOWAK-MICHALSKA, Joanna (Comparative Legilinguistics, 2013)
The article presents a parameter-based method of description of deontic modality in the Polish and Spanish civil codes. The described units are clauses conveying deontic meanings: obligativity, prohibitivity, permissivity and immunitivity. The clauses are excerpted from the corpus on the basis of criteria proposed for this purpose. Clauses conveying deontic meanings are characterized by various properties. Homogeneous properties are classified into parameters (dimensions). As a theoretical framework for a consistent description of the clauses, eight parameters have been proposed on the basis of an analysis of all clauses conveying deontic meanings. The method proposed for describing clauses conveying deontic meanings makes it possible to characterize them systematically and compare them intra- and interlingually. The comparison of the clauses also enables the entire texts of the Polish and Spanish civil codes to be compared